Sacred sustainability as a post-development ethos: Recontextualizing Seyyed Hossein Nasr's metaphysics for Indonesia’s ecological crisis - Santono, Agung Nugroho Reformis; Ulva, Maria; Idlofi; Aji, Kurniawan Seno (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The contemporary ecological crisis in Indonesia reflects not only a failure of governance but a deeper metaphysical rupture caused by the dominance of anthropocentric and extractive development models. While existing literature has extensively discussed Islamic environmental ethics or Seyyed Hossein Nasr’s eco-spirituality separately, there is a scarcity of studies that critically bridge Nasr’s metaphysical traditionalism with modern structural critiques to address the specific political-economic context of Indonesia. This study aims to fill this gap by formulating a